Limitação do requerimento microbiano em energia metabolizável fermentável ou proteína degradável na suplementação do pasto de inverno de vacas da raça Canchim - De Brito, Rodolfo Marques [UNESP]; Moraes Sampaio, Alexandre Amstalden [UNESP]; Da Cruz, Geraldo Maria [UNESP]; De Alencar, Maurício Mello [UNESP]; Franklin Barbosa, Pedro [UNESP]; Taveira Barbosa, Rogério [UNESP] (My University, 2002)
Thirty pregnant Canchim cows were maintained in a rotational grazing system of Marandu grass and received supplemental feed to body weight maintenance during the dry season. With the aim to evaluate the Agricultural and Food Research Council recommendations about supplying dietary substrate to ruminal microbial growth, the animals were allotted to a completely randomized design (3 treatments × 10 replications), according to the following treatments: control (without restriction of microbial requirements of degradable protein and fermentable energy); restriction of microbial requirement of degradable protein; and restriction of microbial requirement of fermentable metabolizable energy. The supplements were composed of corn silage, corn ground and whole soybean, in which determinate amounts were fed daily to animals at 10 a.m. The evaluation period lasted 192 days and the animals were weighed at beginning/end of each one of four experimental subperiods established. The evaluated results indicated that there were no differences on performance of the animals of different treatments with body weight gain of 0. 18, 0.02, and 0. 12 kg/head/day in respective treatments described. It was concluded that the limitation of ruminal microbial growth through reducing of fermentable energy and degradable protein supplies did not affect the performance of Canchim cows during the dry season.
Limitation of microbial requirements of fermentable metabolizable energy or degradable protein in supplementation of winter pasture of Canchim cows
Keywords: Cows; Dry season; Pasture supplementation